PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI SWAY PADA MATERI GOTONG ROYONG DI KELAS IV SEKOLAH DASAR - Fadli, Maulian; Waldi, Atri; Mansurdin; Yesi Anita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is a development research that aims to produce a product in the form of Sway application-based learning media on the material of mutual cooperation in grade IV Elementary School. The development model used is ADDIE, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at SDN 10 Bandar Buat with research subjects of 27 grade IV students. The results of the material validation obtained a percentage of 100% which is included in the valid category. Language validation showed a very high level of feasibility with a percentage of 92.85%. Media validation was carried out by media experts to ensure suitability to the needs of students obtained 91% which is also included in the valid category. In addition, the results of the practicality test from the teacher's response at SDN 10 Bandar Buat obtained 95.83% while the response from students reached 93.20%. The results of the practicality test from the teacher's response at SDN 14 Koto Lalang obtained 91.67% while the response from students reached 90.06%. Then the results of the effectiveness test of SDN 10 Bandar Buat obtained a high category with a total of 0.72191 and the results of the effectiveness test at SDN 14 Koto Lalang obtained the same category with a high category of 0.74175824. Based on the findings above, it can be concluded that the developed learning media is very suitable for use as a learning media based on the Sway application for mutual cooperation material for grade IV Elementary Schools.